Spectral line shape of nonresonant four-wave mixing in Markovian stochastic fields - Bratfalean, R; Ewart, P (1997)
The spectral line shape of the four-wave mixing (FWM) signal, induced by broad bandwidth laser fields, is derived in the case of a nonresonant interaction. The laser fields are assumed to have a Lorentzian spectrum arising from Markovian stochastic fluctuations described by the phase-diffusion, chaotic field, and Gaussian-amplitude models. The usual "phase conjugating" geometry for FWM is considered where the nonresonant interaction is determined only by the statistics of, and the correlations between, the pump and probe fields. For each one of the four possible correlation states between the three input fields and for each of the three fluctuating field models, the line shape of the FWM signal is calculated and shown to be particularly sensitive to the field statistics.